TECHNO-ECONOMIC ANALYSIS OF SOLAR FLAT-PLATE COLLECTOR WORKING WITH NANOFLUID - CHOU, CHOONG YOU (IRC, 2018)
The thermal performance (energetic and exegetic), economic, and environmental aspects of the nanofluid flat plate collector was evaluated. This analysis is carried out across different volumetric concentrations of nanoparticles. By comparing different sizes of nanoparticles, the thermal performance of the collector was compared.